2019
DOI: 10.3390/chemengineering3010002
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Modeling of Silica-Based Membranes and Membrane Reactors for Hydrogen Production and Purification

Abstract: Hydrogen is seen as the new energy carrier for sustainable energy systems of the future. Meanwhile, proton exchange membrane fuel cell (PEMFC) stacks are considered the most promising alternative to the internal combustion engines for a number of transportation applications. Nevertheless, PEMFCs need high-grade hydrogen, which is difficultly stored and transported. To solve these issues, generating hydrogen using membrane reactor (MR) systems has gained great attention. In recent years, the role of silica memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Porous membranes are characterized by pore size, porosity and tortuosity. Generally, pore sizes range from microporous (dp<2nm), mesoporous (2nm<dp<50nm) and macroporous (dp>50nm) (5). For this study, ceramic membranes are chosen due to their versatility (for use in separation and reaction processes), high stability, long life-span, compact size, low energy demand, high efficiency and high resistance to aggressive chemical environment or harsh environmental conditions of temperature and pressure which prevail in industry.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Porous membranes are characterized by pore size, porosity and tortuosity. Generally, pore sizes range from microporous (dp<2nm), mesoporous (2nm<dp<50nm) and macroporous (dp>50nm) (5). For this study, ceramic membranes are chosen due to their versatility (for use in separation and reaction processes), high stability, long life-span, compact size, low energy demand, high efficiency and high resistance to aggressive chemical environment or harsh environmental conditions of temperature and pressure which prevail in industry.…”
Section: Theorymentioning
confidence: 99%
“…Figure 1 Experimental set-up showing all equipment including pressure gauge (1), membrane module covered with heating tape (2), gas regulator (3), gas cylinder (4), heat regulator(5), volumetric meter(6) and temperature indicator(7) …”
mentioning
confidence: 99%
“…Table 1 shows the summary of the key review studies published in journals in the last 5 years. 5,7,[17][18][19][20][21][22][23][24][25][26][27] These review studies give general information on the MRs and their applications, Pd-based membranes and their permeability, different MR configurations, recent progress in MR technology, effects of operating parameters on the MR performance, and alternative fuel production using MR. The literature survey on the review papers on the MRs published in the last 5 years showed that, according to the author's best knowledge, there is no comprehensive review study on the mathematical modeling of the hydrogen production from steam methane reforming through MRs.…”
Section: Introductionmentioning
confidence: 99%
“…Although mixed matrix membranes have shown promising performance under laboratory tests, their commercialization requires stable performance under harsh conditions . Compared to inorganic membranes, they have much greater chemical and thermal chemical permanency, good corrosion resistance, and high‐pressure constancy . Alumina membranes have been used as mesoporous membranes where separation takes place by the Knudsen diffusion mechanism .…”
Section: Introductionmentioning
confidence: 99%
“…15 Compared to inorganic membranes, they have much greater chemical and thermal chemical permanency, good corrosion resistance, and high-pressure constancy. 16,17 Alumina membranes have been used as mesoporous membranes where separation takes place by the Knudsen diffusion mechanism. 18,19 However, the use of alumina membranes has become limited because its selectiveness in terms of region makes it inadequate, and the rate of diffusion is restrained by its molecular weight.…”
Section: Introductionmentioning
confidence: 99%